Crying Among Helping Professionals: A Cross-Cultural Study of Emotional Expression - Ágota Pap (Universitas Negeri Surabaya, 2025)
Background: Crying is a universal but understudied emotional expression serving intrapersonal and interpersonal functions such as stress regulation, empathy, and social bonding. Although therapist crying in sessions has been explored, little is known about how helping professionals experience and regulate crying beyond therapy. Understanding these patterns is crucial for promoting professional well-being and recognizing culturally shaped emotions. Objective: This study examined the prevalence, contextual factors, and cultural patterns of crying among helping professionals, and its links with self-awareness and life satisfaction. Methods: Ninety Serbian- and Hungarian-speaking therapists from Vojvodina completed the Adult Crying Inventory (ACI), Satisfaction With Life Scale (SWLS), and a demographic questionnaire. Analyses included descriptive statistics, t-tests, correlations, and ANOVA. Results: Women cried more often than men; crying decreased with age and experience. Married individuals showed higher life satisfaction. Hungarians reported crying alone more often and in response to unmet expectations, while Serbians cried more in others’ presence. Conclusion: Crying among helping professionals reflects emotional, demographic, and cultural dynamics, underscoring the need for emotional self-awareness and resilience in professional training. Abstrak Latar Belakang: Menangis adalah ekspresi emosional universal namun kurang diteliti, yang berfungsi secara intrapersonal dan interpersonal, termasuk pengaturan stres, empati, dan ikatan sosial. Meskipun tangisan terapis dalam sesi telah dipelajari, sedikit diketahui tentang bagaimana profesional bantuan mengalami dan mengatur tangisan di luar konteks terapi. Memahami pola ini penting untuk meningkatkan kesejahteraan profesional dan mengenali ekspresi emosi yang dipengaruhi budaya. Tujuan: Penelitian ini menelaah prevalensi, faktor kontekstual, dan pola budaya menangis di antara profesional bantuan, serta hubungannya dengan kesadaran diri dan kepuasan hidup. Metode: Sembilan puluh terapis berbahasa Serbia dan Hungaria di Vojvodina mengisi Adult Crying Inventory (ACI), Satisfaction With Life Scale (SWLS), dan kuesioner demografis. Analisis mencakup statistik deskriptif, t-test, korelasi, dan ANOVA. Hasil: Perempuan menangis lebih sering dibandingkan laki-laki; frekuensi menurun seiring usia dan pengalaman. Individu menikah menunjukkan kepuasan hidup lebih tinggi. Partisipan Hungaria lebih sering menangis sendirian, sedangkan partisipan Serbia lebih sering di hadapan orang lain. Kesimpulan: Menangis pada profesional bantuan mencerminkan dinamika emosional dan budaya, menegaskan pentingnya kesadaran emosional dan ketahanan dalam pelatihan profesional.